Novel alleles of rice eIF4G generated by CRISPR/Cas9-targeted mutagenesis confer resistance to Rice tungro spherical virus - Macovei, Anca; Sevilla, Neah R.; Cantos, Christian; Jonson, Gilda B.; Slamet-Loedin, Inez; Čermák, Tomáš; Voytas, Daniel F.; Choi, Il-Ryong; Chadha-Mohanty, Prabhjit (Wiley, 2018)
Rice tungro disease (RTD) is a serious constraint in rice production across tropical Asia. RTD is caused by the interaction between Rice tungro spherical virus (RTSV) and Rice tungro bacilliform virus. RTSV resistance found in traditional cultivars has contributed to a reduction in the incidence of RTD in the field. Natural RTSV resistance is a recessive trait controlled by the translation initiation factor 4 gamma gene (eIF4G). The Y1059V1060V1061 residues of eIF4G are known to be associated with the reactions to RTSV. To develop new sources of resistance to RTD, mutations in eIF4G were generated using the CRISPR/Cas9 system in the RTSV‐susceptible variety IR64, widely grown across tropical Asia. The mutation rates ranged from 36.0% to 86.6%, depending on the target site, and the mutations were successfully transmitted to the next generations. Among various mutated eIF4G alleles examined, only those resulting in in‐frame mutations in SVLFPNLAGKS residues (mainly NL), adjacent to the YVV residues, conferred resistance. Furthermore, our data suggest that eIF4G is essential for normal development, as alleles resulting in truncated eIF4G could not be maintained in homozygous state. The final products with RTSV resistance and enhanced yield under glasshouse conditions were found to no longer contain the Cas9 sequence. Hence, the RTSV‐resistant plants with the novel eIF4G alleles represent a valuable material to develop more diverse RTSV‐resistant varieties.